(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2024)
Abstract: The mining industry, despite its contributions to the economy of many countries, including developing ones, has caused significant damage to the environment. In this study, gold tailings were used as a potential alternative for natural sand in brick manufacturing. The materials and bricks made from these materials were evaluated both mechanically and environmentally, through particle size distribution, water absorption, compressive strength, and leaching characteristics. The results showed that the particle size of gold tailings was less than 2 mm, with a high percentage of silicon dioxide (71.8%). The compressive strength of the bricks made from gold tailings replacements ranged from 11.67 to 22.33 MPa, with the most promising strength being in T25% replacement. In terms of environmental leaching, the study revealed that most gold tailings replacements did not show any metal leaching, and the levels of metals detected were significantly low. There fore, this study concluded that using gold tailings as a replacement for natural sand in construction industries is a viable and promising alternative. This practice can reduce the disposal of gold tailings on mine sites, contributing to a more sustainable mining industry